Factors Shaping MBA Students’ Enrollment in Foreign-Affiliated Colleges - Pradhanang, Sunetra; Panthi, Suresh; Shrestha, Avinash (Nexus: Journal of Interdisciplinary Engineering, Technology and Management, 2026)
Based on participants’ accounts, the growing demand for internationally recognized business qualifications in Nepal has led to a rapid expansion of internationally affiliated MBA institutions in Kathmandu; however, there is limited evidence on the factors influencing participants’ choices of these institutions in the local context. The present study aims to explore the determinants shaping MBA participants’ selection of internationally affiliated institutions in Kathmandu. A qualitative research design was employed using semi-structured interviews with 20 MBA participants enrolled in internationally affiliated institutions. An interview guide consisting of open-ended questions on motivations, information sources, perceived quality, social influence, financial considerations, and challenges was used. Data were transcribed and analyzed using thematic analysis, including coding, categorization, and theme development. The findings show that participants primarily choose internationally affiliated MBA programs for the perceived international recognition of degrees, locally accessible global education, practical, modern curricula, and expectations of improved career prospects. Family support, peer recommendations, and affordability compared to studying abroad were also notable contextual influences in the Nepalese setting. This research implies that institutions should strengthen transparency regarding degree recognition, emphasize employability outcomes, and align curricula with industry needs. At the same time, policymakers should enhance regulation and quality assurance of foreign affiliations. By situating institution-choice theory in Nepal, this study highlights context-specific drivers of demand for transnational higher education in developing-country settings.